2003
DOI: 10.1172/jci15598a1
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and prolonged vasoconstrictor signaling in RGS2-deficient mice

Abstract: The authors wish to add the following information. Table 1: The doses of antagonists used to treat wild-type and RGS2-knockout mice were hexamethonium at 5 mg/kg i.v., prazosin at 200 µg/kg i.v., and candesartan at 100 µg/kg i.v. Effective ganglionic blockade by hexamethonium was established as described previously, whereas blockade by prazosin or candesartan was demonstrated by the inability of a subsequent infusion of phenylephrine (10 µg/kg i.v.) or angiotensin II (1 µg/kg i.v.) to increase blood pressure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 0 publications
2
72
1
2
Order By: Relevance
“…The effect on RGS modulation resembles the results we obtained after poly(I:C) stimulation, thus proving the responsibility of the TRIF activation for the upregulation of both RGS mRNA. Stimulation of TLR3 and activation of the TRIF pathway leads to interferon-b production [35]. Takaoka et al [36] demonstrated that interferon-b can induce the transcription of p53 and this is critical for an antiviral defence of the host.…”
Section: Discussionmentioning
confidence: 99%
“…The effect on RGS modulation resembles the results we obtained after poly(I:C) stimulation, thus proving the responsibility of the TRIF activation for the upregulation of both RGS mRNA. Stimulation of TLR3 and activation of the TRIF pathway leads to interferon-b production [35]. Takaoka et al [36] demonstrated that interferon-b can induce the transcription of p53 and this is critical for an antiviral defence of the host.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, genes that encode RGS proteins 2, 4, and 5 are clustered on a locus of chromosome 1 that has been associated with the development of hypertension in different ethnic groups (13). In line with this, the genetic ablation of RGS2 in mice causes hypertension (14), whereas loss of RGS5-a potent inhibitor of Ga q/11 and Ga i/o activityresults in hypotensive (15), normotensive (16), and hypertensive (17,18) animals, depending on their genetic background. As can be deduced from these divergent results, the functional role of RGS5 in the regulation of blood pressure, the VSMC phenotype, and arterial remodeling seem to be context dependent and are still debated.…”
mentioning
confidence: 88%
“…Previous studies described phenotypic differences in VSMCs derived from CNC-and mesenchyme-derived VSMCs (5). Data from our group and others suggested that RGS proteins are important regulators of G-protein signaling in VSMCs (12,27). Accordingly, we here used real-time RT-PCR to determine whether differences in RGS isoform expression in the common carotid artery (CNC derived) and descending (abdominal) aorta (mesenchyme derived) may contribute to known phenotypic differences in VSMCs from different developmental origins ( Fig.…”
Section: Rgs5 Mrna Expression Varies Widely Among Different Vascular mentioning
confidence: 99%